The Influence of Environmental, Social, Governance on Company Financial Risks: A Study on LQ-45 - Ramadhan, Muhammad Farhan; Achsani, Noer Azam; Andati, Trias (Indonesian Journal of Multidisciplinary Science, 2023)
This study aims to see the consequence of environmental, social, and governance (ESG) performance on LQ-45firm’s financial risk. This study uses a 23 sample of LQ-45 firms from 2016 to 2020 and applies Generalized Method of Moment (GMM) analysis. The studies find an adverse effect of ESG Performance and firm’s risk. Controversies on ESG also adversely influences the firm’s risk. However, there is no significant effect on board gender diversity on financial risk of the firm. Also, These findings are in line with stakeholder, signaling, Legitimacy, and risk management theory. The firms that perform reasonably on ESG have lower total risk. However, the firm’s negligence on ESG and involvement in ESG Controversies moderates the ESG-total risk nexus. The findings will help investor and portofolio managers evaluate how ESG, ESG Controversies, and Board Gender Diversity influence firm’s financial risk and help them make a better investment decisions. Additionally, regulators can revise the ESG and ESG Controversy disclosure criteria and make them accessable to all stakeholders for better decision making.